Effect of decision parameter efficiency on target reliability - Andrew Way; Nico de Koker; Celeste Viljoen (Acta Polytechnica CTU Proceedings, 2022)
Target reliability forms the basis of most modern design standards and is intended to represent an optimal balance of safety and risk of failure. Previous research noted discrepancies between target reliability obtained using generic and case-specific cost optimization for SLS cases. The source of the discrepancies was identified as the efficiency of the decision parameter at increasing reliability. This research extends the investigation to cases of ULS failures and found similar discrepancies. Generic cost optimization assumes a linear dependence between the decision parameter and the structural resistance. Where the dependence of resistance on the decision parameter is superlinear, the generic was found to under-predict target reliability by up to 15%. A factor is proposed to adjust generically-obtained ULS target reliability to be more appropriate to specific ULS cases. The factor accounts for the efficiency of the decision parameter, the case-specific cost of safety and parameter variation. The adjustment factor represents a first step towards mapping generic to case-specific target reliability in the ideal of promoting safer and more cost-effective structures.